As consequências econômicas e sociais do governo Nicolás Maduro: uma abordagem com controle sintético - Dantas, Ricardo Alessandro (2024)
This work seeks to analyze the impacts of the election of Nicolás Maduro on economic and social indicators in Venezuela. It uses the synthetic control methodology developed by Abadie and Gardeazabal (2003), Abadie, Diamond and Hainmueller (2010) and Abadie, Diamond e Hainmueller (2015). Regarding the effects on GDP per capita, there is a sharp drop in Venezuela in relation to the synthetic control, representing a difference of US$ 11,310 in 2019. The Venezuelan results also show worse performances for the TFP, wellfare and the Indexes of Monetary and Business Freedom, as well as for for indexes related to health: Life Expectancy and Infant Mortality. Therefore, it can be inferred that the government of Nicolás Maduro generated negative economic and social consequences for the Venezuelan population, by negatively influencing the group of variables studied.